2012
DOI: 10.1111/j.1937-5956.2011.01297.x
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Appointment Rule in the Presence of No‐Shows and Walk‐Ins

Abstract: This study introduces a universal “Dome” appointment rule that can be parameterized through a planning constant for different clinics characterized by the environmental factors—no‐shows, walk‐ins, number of appointments per session, variability of service times, and cost of doctor's time to patients’ time. Simulation and nonlinear regression are used to derive an equation to predict the planning constant as a function of the environmental factors. We also introduce an adjustment procedure for appointment syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 40 publications
(84 reference statements)
1
91
0
2
Order By: Relevance
“…Research on how to manage waiting lists has mainly focused on mathematical models that help hospitals better manage resources. Queuing theory has been the most common methodology applied, and the possibility of missed appointments has been taken into account in these models (Cayirli, Yang & Quek, 2012;Green, 2010;Green & Yankovic 2011;Liu, 2016).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Research on how to manage waiting lists has mainly focused on mathematical models that help hospitals better manage resources. Queuing theory has been the most common methodology applied, and the possibility of missed appointments has been taken into account in these models (Cayirli, Yang & Quek, 2012;Green, 2010;Green & Yankovic 2011;Liu, 2016).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Only a few recent studies consider the appointment scheduling systems of the clinics accepting walk-in patients (Cayirli et al, 2006(Cayirli et al, , 2008(Cayirli et al, , 2012Kim and Giachetti, 2006;LaGanga and Lawrence, 2008). Cayirli et al (2006Cayirli et al ( , 2008 investigate the performance of appointment scheduling rules (ASRs) in outpatient clinics in terms of patient waiting time and provider idle time and overtime.…”
Section: Outpatient Appointment Scheduling Considering Overbooking Anmentioning
confidence: 97%
“…In primary-care clinics with many walkin patients and high no-show rates or high late-cancellation rates, policies such as overbooking (i.e., scheduling more appointments than provider capacity in each clinic session) and accepting walkin patients are often adopted to improve provider utilization and clinic accessibility. In the literature, many studies propose quantitative models to analyze or optimize overbooking policies (Kopach et al, 2007;Lawrence, 2007, 2012;Muthuraman and Lawley, 2008;Kros et al, 2009;Zeng et al, 2010;Ratcliffe et al, 2012), and also several studies investigate the appointment scheduling systems in the clinics accepting walk-in patients (Cayirli et al, 2006(Cayirli et al, , 2008(Cayirli et al, , 2012Kim and Giachetti, 2006;LaGanga and Lawrence, 2008). In the literature studies considering walk-in patients, it is assumed that a clinic accepts all walk-in patients, and that the cost structure for walk-in patients is same as that for patients with appointments scheduled.…”
Section: Introductionmentioning
confidence: 98%
“…No-show adversely affects productivity and overall cost. Cayirli et al (2012) suggested a dome rule for fixing appointment times while taking care of different interruptions generally experienced in day to day operations of healthcare organisations. LaGanga and Lawrence (2012) came up with an appointment system which could overbook appointment schedules in a way that revenue generated from serving extra patients could balance the negative effects of increased patient waiting time and physician overtime costs.…”
Section: Appointment Schedulingmentioning
confidence: 99%